Efeitos da Angiotensina-(1-7) e Angiotensina II no inotropismo cardíaco e vasomotricidade coronariana: um complexo envolvimento entre os receptores angiotensinérgicos - Nunes, Allancer Divino de Carvalho (2018)
Despite Angiotensin-(1-7) [Ang-(1-7)] and Angiotensin II (Ang II) be considered important regulators of the cardiovascular system, its direct effects on cardiac contractility remain unclear and even controversial. Several studies, using different preparations, have showed that Ang-(1-7) or Ang II produce positive, negative or no inotropic effects. Thus, the aim of this study was to increase the knowledge about the effect of the low concentration of Ang-(1-7) and Ang II on cardiac contractility, coronary vascular function and the possible receptors and mechanisms of action involved in these effects. The in vivo effects of Ang-(1-7) and Ang II on cardiac contractility were evaluated in anesthetized rats. The Ang-(1-7) 4 nmol/L and Ang II 40 nmol/L caused negative inotropism in anesthetized rats. None of the peptides were able to change heart rate or arterial blood pressure in anesthetized rats. The direct effects of the Ang-(1-7) and Ang II on cardiac contractility were evaluated in isolated perfused rat hearts. After a basal period (30-40 minutes), the hearts were perfused for an additional 15 min with Ang-(1-7) and Ang II (20 pmol/L) in presence or absence of Mas receptor antagonist A-779 (2 nmol/L), AT2 receptor antagonist PD1233190 (2 nmol/L), AT1 receptor antagonist Losartan (1μmol/L), MrgD receptor antagonist D-PRO (2 nmol/L), ACE2 inhibitor DX600 (2nmol/L), Nitric Oxide synthase (NOS) inhibitor L-Name (10 nmol/L), Guanylyl cyclase (GC) inhibitor ODQ (200 nmol/L) and Adenylyl cyclase (AC) inhibitor MDL 12,330A (1μmol/L). Low concentrations of Ang-(1-7) and Ang II reduced the left ventricular end-systolic pressure (LVESP). The A-779 did not blocked the effect of Ang-(1-7) or Ang II. PD123319 and Losartan inhibited the Ang-(1-7) but not Ang II-induced negative inotropic effects. On the other hand, D-PRO was able to block the negative inotropic effect of the Ang II and Ang-(1-7). Furthermore, L-Name, ODQ and MDL 12,330A inhibited the Ang-(1-7) but not Ang II-induced negative inotropic effects. Similarly, low concentrations of Ang- (1-7) and Ang II-induced coronary vasodilatation. The A-779, D-PRO, L-Name, MDL 12,330A blocked the effect of Ang-(1-7) or Ang II. The DX600 blocked the vasodilatation induced by Ang II. PD123319, Losartan and ODQ inhibited the Ang-(1-7) but not Ang II-induced coronary vasodilatation. In addiction, the pharmacological blocked and gene silencing of AT1 receptor in endothelial human cells stimulated with Ang-(1-7) decreased AKT phosphorilation induced by Ang-(1-7). These data demonstrate that Ang-(1-7) and Ang II, at picomolar concentrations, induce significant and similar negative inotropic and coronary vasodilatation effects involving complex interaction mechanisms between many different receptors, altering intracellular signaling and their constitutive activity.